Estimation of Thai Adult Age by Dental Root Translucency and Periodontosis - Dulabutr, Duangta; Plodprong, Chatchadaporn (Srinagarind Medical Journal, 2019)
Background and objective: To determine Thai adult age by analyzing dental root translucency and periodontosis for using in unknown dead body. Methods: A cross-sectional study of 398 teeth from 345 Thai adult with known actual chronological age was conducted. The root translucency height (t), periodontosis height (p), and root height (r) were measured using the Lamendin’s technique. Sex, age, tooth types and tooth positions were analyzed by descriptive statistics. The correlation between age and three tooth parameters were analyzed by Pearson's correlation and multiple regression analysis using statistical significance at p<0.05. Results: Dental root translucency and periodontosis were able to estimate Thai adult age with statistical significance (p<0.001). The proposed equation derived from multiple regression analysis was Age = 16.038 + (0.572 x P) + (0.567 x T), where (P = p*100/r, T = t*100/r). The mean error was ±5.2 years. In addition, Thai formula for male and female were Age = 13.816 + (0.669 x P) + (0.57 x T) and Age = 17.449 + (0.505 x P) + (0.567 x T), respectively when sex was known. These Thai formulas showed a better precision in the young adult (20-50 years old). Conclusion: Single tooth was able to estimate Thai adult age by using dental root translucency and periodontosis parameters in all tooth types and positions with a simple method.